Natural convection in nanofluid filled and partially heated annulus: Effect of different arrangements of heaters - Bouzerzour, Abdeslem; Djezzar, Mahfoud; Öztop, Hakan Fehmi; Tayebi, Tahar; Abu-Hamdeh, Nidal (Elsevier, 2020)
The natural convection in a Cu-water nanofluid filled and partially heated annulus between two elliptical cylinders is numerically analyzed. A cold temperature T T is imposed on the outer cylinder while heaters are placed on the inner cylinder wall in three different configurations. The flow governing equations are written under the Vorticity-Stream function dimensionless formulation and solved with a developed code using FORTRAN platform. The results are given by the finite-volume method in the ranges of Rayleigh number (10(3)<10(5)) and volume fraction (0<0.08). The presented isotherms and streamline contours with average and local Nusselt numbers graphs show an enhancement of heat transfer by increasing Rayleigh number or nanoparticles volume fraction. Placing the heaters on the left and the right sides of the inner cylinder wall gives better heat transfer performances. (C) 2019 Published by Elsevier B.V.
Keywords: Partial heating; Annulus; Elliptic cylinders; Nanofluid